2005
DOI: 10.1097/01.pas.0000169499.96658.6e
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Heilmannii Gastritis

Abstract: H. heilmannii belongs to the Helicobacter family and is found in a small number of gastric biopsies. This bacterium is generally found in primates, cats, pigs, and carnivorous mammals. About 0.5% to 6% of human gastric infections have been attributed to H. heilmannii. The bacterium usually induces mild chronic gastritis but may be associated with peptic ulceration, and rare cases were reported in association with gastric carcinoma and mucosa-associated lymphoid tissue lymphoma. We report a case of H. heilmanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…6f ). Coinfection with several species of Helicobacter bacteria (the so-called H. heilmannii -like organisms) may yield positive results for H. pylori in IHC analysis 129 , 130 , 131 , 132 . For the precise identification of Helicobacter species, PCR and other molecular techniques can be used.…”
Section: Bacterial Infectionmentioning
confidence: 99%
“…6f ). Coinfection with several species of Helicobacter bacteria (the so-called H. heilmannii -like organisms) may yield positive results for H. pylori in IHC analysis 129 , 130 , 131 , 132 . For the precise identification of Helicobacter species, PCR and other molecular techniques can be used.…”
Section: Bacterial Infectionmentioning
confidence: 99%
“…Helicobacter heilmannii , a Gram‐negative rod bacterium that belongs to the Helicobacter family, which includes Helicobacter pylori , is characterized by a relatively large size (5–9 μm) and a corkscrew appearance. Helicobacter heilmannii is located in the stomachs of primates, cats, pigs, and humans (Singhal & Sepulveda, 2005), and causes gastritis, peptic ulcer, acute gastric mucosal lesion, gastric carcinoma, and mucosa‐associated lymphoid tissue (MALT) lymphoma in humans (Okiyama et al , 2005). Previously, rRNA and urease gene sequence analysis revealed that ‘ H. heilmannii ’ is not a single species, but includes H. heilmannii type‐1 and H. heilmannii type‐2 strains (O'Rourke et al , 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic gastritis was the most common histologic finding in our cohort, employing a well-validated gastritis scoring tool (i.e., the Updated Sydney system), consistent with previous reports. 9,22,23,[35][36][37][38][39] Compared to H. pylori, H. heilmannii-associated chronic gastritis is considered to be more focal, milder, and restricted to the antrum. 40 In our study, we also found H. heilmanniiassociated chronic gastritis to have a milder degree of inflammation compared with H. pylori.…”
Section: Discussionmentioning
confidence: 99%